Clinical Efficacy of Subgingivally Delivered Punica Granatum Chip and Gel in Management of Chronic Periodontitis Patients - Tyagi, P.; Dodwad, V. M.; Vaish, S.; Chowdhery, T.; Gupta, N.; Kukreja, J. B. (Kathmandu University Medical Journal, 2020)
Background Periodontitis has a multifactorial etiology, and the pathogenic bacteria that reside in the subgingival area are the primary etiologic agent. Objective The study aimed to evaluate the clinical efficacy and benefits of herbal chip and gel made from extracts of Punica granatum as a subgingival adjunct to scaling and root planing (SRP). Method A randomized control clinical trial was conducted on 30 systemically healthy patient’s sites having chronic periodontitis, and they were randomly allocated to into three treatment groups followed by Scaling and Root Planing in all patients. Group 1 - Ten patients received Scaling and Root Planing and Punica granatum chip at selected sites. Group 2 - Ten patients received Scaling and Root Planing and punica granatum gel at selected sites. Group 3 - Ten patients with Scaling and Root Planing alone. Clinical parameters were recorded at baseline, 21 days and at 45 days which included plaque index (PI), gingival index (GI), probing pocket depth (PPD) and relative attachment level (RAL). Result Plaque Index and Gingival index showed better reduction in group I compared to group II and group III at 21st day 45th day follow up. Analysing Pocket Probing Depth the intergroup comparison revealed similar results with maximum reduction being seen in group I from baseline to 21 and baseline to 45 days (p < 0.001). On analysing Relative Attachment Loss revealed reduction in all three groups with maximum reduction in group I from baseline to 45 days and reduction in group III was not statistically significant (p < 0.090). Conclusion The study concluded that Punica granatum chip as an adjunct to Scaling and Root Planing was more effective than Punica granatum gel and scaling and root planing alone.